CLINICAL EVALUATION OF THE ERRORS OF FIXED PROSTHODONTIC IMPRESSIONS - Steliana-Gabriela Buștiuc; Raluca Briceag; Gheorghe Raftu; Elena-Claudia Sin; Mihaela-Macrina Mihalache; Camer Salim; Aureliana Caraiane (Romanian Journal of Oral Rehabilitation)
The precise transfer of the elements of the prosthetic field requires a good knowledge of soft and hard tissue anatomy, especially in the area of the cervical finish line. Dentists also need to understand how to select gingival retraction methods, but also how to properly handle impression materials. The purpose of this study was to evaluate clinically detectable errors commonly seen in impressions for fixed prosthodontic restorations Materials and methods A number of 194 dental impressions were examined that were registered with the aim of making fixed prosthetic restorations. The dental impressions were collected between January 2023 and April 2024 and came from several dental offices in Constanța. Impressions were evaluated by visual inspection under conventional light by dentists specializing in dental prosthodontics. For each impression, the errors recorded during the examination were noted, regarding: the overall imperfections, the uniformity of the impression material and the finish line of the dental preparations. Results Errors were detected in 147 impressions. Overall poor details of dental impression were noted in 42 (41,58%) impressions. Inadequate impression material mixing was recorded in 21 – 14,29% impressions and the most of them were condensation-type silicones impression. The most common error seen in examined impression consisting of inadequate retention (36.73%). The most frequent types of errors recorded in the finish line were represented by bubbles, being found in 66.67% of cases. Conclusions Despite the improvement of techniques and materials, there is still a significant percentage of errors of fixed prosthesis impressions. The reduction of impression errors in fixed prosthodontics can be done by a good knowledge of the impression technique and a good selection of impression materials and trays. The management of the gingival sulcus tissues is also particularly important.